Life of Galileo - Brecht, Bertolt,Willett, John,Rorrison, Hugh (Bloomsbury Publishing Plc, 2008)
Cover – Contents – Bertolt Brecht 1898-1956 – Plot – Commentary – Moral – History – Galileo – Minor characters – Epic theatre – Language – Staging – Meaning – Further reading – LIFE OF GALILEO – Notes – Questions for further study.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books